Aktivitas Antimikroba in Vitro Senyawa Turunan Fumarat dan Kajian Hubungan Struktur-Aktivitasnya = Antimicrobial Activity in vitro of Fumaric Derivatives and Their Structure-Activity Relationship Analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstrak One of the problems in infection therapy is the existence of drugs resistance strains for most of antimicrobial drugs currently used in clinic practice. Therefore, it is important to find new antimicrobial candidate compounds, particularly new leads, which would be able to become the basis for developing new drugs. The purpose of this study is to evaluate antimicrobial activity and perform Quantitative Structure-Activity Relationships (QSAR) of a series (nine compounds) of fumaric derivates. Those compounds are: ethyl-N-phenyl fumaramate (A), methyl-N-phenyl fumaramate (B), ethyl-N-benzyl fumaramate (C), methyl-N-anisyl fumaramate (D), methyl-N-benzyl fumaramate (E), ethyl-N-anisyl fumaramate (F), Ca-benzyl fumaramate(G), Na-benzyl fumaramate(H), N-benzyl-propyl-fumaramate (I). The compounds were assayed in vitro for antimicrobial activity using macrobroth dilution method against bacteria Pseudomonas aeruginosa and Salmonella enteritidis, and three strains of fungi i.e: Aspergillus niger, Penicillium sp and Candida albicans. The minimum inhibitory concentration (MIC) was determined for the tested compounds as a parameter of activity. QSAR analysis between atomic net charges (q) as predictors and antifungal activity in the form of log (1/MIC) was performed by computational chemistry method using semi-empirical molecular orbital AMI calculation. q2 q3^^ Ftabie = 54-09)- Penicillium sp: Log 1/KHM = -14.921 + 2.175.(qC6) + 201.464.(qC10) + 158.076.(qO2) - 11.115. (qO3)